The gut microbiota‐aromatic hydrocarbon receptor (AhR) axis mediates the anticolitic effect of polyphenol‐rich extracts from Sanghuangporus - Shi Zhong; Yu‐Qing Sun; Jin‐Xi Huo; Wen‐Yi Xu; Ya‐Nan Yang; Jun‐Bo Yang; Wei‐Jie Wu; Yong‐Xin Liu; Chong‐Ming Wu; You‐Gui Li (iMeta, 2024)
Abstract Inflammatory bowel disease (IBD) is a significant global health concern. The gut microbiota plays an essential role in the onset and development of IBD. Sanghuangporus (SH), a traditional Chinese medicinal mushroom, has excellent anti‐inflammatory effects and is effective at modulating the gut microbiota. Despite these attributes, the specific anticolitic effects of SH and the mechanisms through which the gut microbiota mediates its benefits remain unclear. Herein, we demonstrated that polyphenol‐rich extract from SH effectively alleviated the pathological symptoms of dextran sodium sulfate (DSS)‐induced colitis in mice by modulating the gut microbiota. Treatment with SH distinctly enriched Alistipes, especially Alistipes onderdonkii, and its metabolite 5‐hydroxyindole‐3‐acetic acid (5HIAA). Oral gavage of live A. onderdonkii or 5HIAA potently mitigated DSS‐induced colitis in mice. Moreover, both 5HIAA and SH significantly activated the aromatic hydrocarbon receptor (AhR), and the administration of an AhR antagonist abrogated their protective effects against colitis. These results underscore the potent efficacy of SH in diminishing DSS‐induced colitis through the promotion of A. onderdonkii and 5HIAA, ultimately activating AhR signaling. This study unveils potential avenues for developing therapeutic strategies for colitis based on the interplay between SH and the gut microbiota.